HUMAN FACTORS ENGINEERING FOR MITIGATING INDUSTRIAL HYGIENE HAZARDS IN MALAYSIAN LABORATORIES AND MANUFACTURING ENVIRONMENTS (Journal of Energy and Safety Technology (JEST), 2025)
This study explores the integration of human factors engineering (HFE) into industrial hazard mitigation, with focus on ergonomic adjustment, noise reduction, and chemical exposure. Recognizing the limitations of conventional safety measures, the research identifies ergonomic risks and auditory hazards as critical factors affecting worker safety and operational efficiency. Through a mixed-method approach, including observational studies and statistical analysis, effective HFE interventions are designed and assessed. Results indicate that tailored ergonomic solutions and noise control strategies significantly enhance hazard mitigation. The study advocates for a systemic application of HFE principles in industrial settings, emphasizing the role of comprehensive ergonomic assessments and proactive noise management in mitigating risks. The conclusions drawn underscore the potential of HFE to revolutionize safety protocols and suggest avenues for future research in advancing industrial health and safety measures.
Keywords: Human Factors Engineering; Industrial Hazard Mitigation; Ergonomics; Noise Control; Chemical Safety